ChemInform Abstract: Single‐Electron‐Transfer (SET)‐Induced Oxidative Biaryl Coupling by Polyalkoxybenzene‐Derived Diaryliodonium(III) Salts. Issue 14 (8th April 2014) - Yamaoka, Nobutaka; Sumida, Kohei; Itani, Itsuki; Kubo, Hiroko; Ohnishi, Yusuke; Sekiguchi, Sho; Dohi, Toshifumi; Kita, Yasuyuki
Abstract The title reaction proceeds without a metal catalyst by a unique mechanism involving SET oxidation by means of aryliodonium salts followed by electron‐rich aryl transfer.